2011
DOI: 10.2119/molmed.2011.00278
|View full text |Cite
|
Sign up to set email alerts
|

Serum from Patients Undergoing Remote Ischemic Preconditioning Protects Cultured Human Intestinal Cells from Hypoxia-Induced Damage: Involvement of Matrixmetalloproteinase-2 and -9

Abstract: Remote ischemic preconditioning (RIPC) can be induced by transient occlusion of blood flow to a limb with a blood pressure cuff and exerts multiorgan protection from ischemia/reperfusion injury. Ischemia/reperfusion injury in the intestinal tract leads to intestinal barrier dysfunction and can result in multiple organ failure. Here we used an intestinal cell line (CaCo-2) to evaluate the effects of RIPC-conditioned patient sera on hypoxia-induced cell damage in vitro and to identify serum factors that mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
3
20
1
Order By: Relevance
“…The release of a circulating factor with a rapid onset of cardioprotection in the bioassay heart of the present study is consistent with prior experimental and clinical studies, which revealed evidence for protection with an interval of only 5 to 10 min between the RIPC stimulus and the injurious event 22, 23, 37, 38. The continuous presence of a circulating factor that provides cardioprotection in the bioassay mouse heart in the present study is again consistent with prior experimental and clinical studies, which revealed evidence of long-lasting protection 24, 26, 27, 39 for up to 1 week after the RIPC stimulus (28).…”
Section: Discussionsupporting
confidence: 91%
“…The release of a circulating factor with a rapid onset of cardioprotection in the bioassay heart of the present study is consistent with prior experimental and clinical studies, which revealed evidence for protection with an interval of only 5 to 10 min between the RIPC stimulus and the injurious event 22, 23, 37, 38. The continuous presence of a circulating factor that provides cardioprotection in the bioassay mouse heart in the present study is again consistent with prior experimental and clinical studies, which revealed evidence of long-lasting protection 24, 26, 27, 39 for up to 1 week after the RIPC stimulus (28).…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the underlying pathways of RIPC, we showed that serum taken from patients after RIPC had a different capability of protecting cells during hypoxia than the serum taken before RIPC, and the involvement of matrix-metalloproteinases 2 and 9 in the mechanism conferring protection was demonstrated in the serum taken after RIPC [31]. These data support the idea that humoral factors are involved in RIPC-mediated effects.…”
Section: Discussionsupporting
confidence: 64%
“…Our data also add to the growing evidence that serum from human subjects who have undergone healthy lifestyle interventions can confer cellular protection [37][38][39][40][41][42]. In general, beneficial changes in cellular phenotypes cannot be attributed to changes in anyone (or several) circulating factors.…”
Section: Discussionmentioning
confidence: 56%